Kebijakan Artificial Intelligence (AI) dalam Pembelajaran di Perguruan Tinggi - Anggi Fatmadiwi; Suryani; Hartoyo, Agung; Erlina, Erlina (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The rapid development of information and communication technology has made artificial intelligence (AI) a crucial issue in education and learning. Higher education institutions face challenges in adopting AI into the learning process to enhance the quality of technology-based education. This study aims to analyze policies and regulations, implementation, and evaluation of AI utilization in higher education learning. The method used is a literature study with data collection techniques based on primary and secondary sources relevant to artificial intelligence. Data analysis was conducted using a descriptive analysis method. The results of the study indicate that the implementation of generative AI in learning presents both opportunities and challenges. On one hand, generative AI technology can assist the academic community in accessing information and improving learning efficiency. However, improper use may negatively impact academic integrity. Therefore, appropriate policies and regulations are necessary for higher education institutions to address challenges and optimize AI integration in the learning process.